Daratumumab for treatment‐refractory antibody‐mediated diseases in neurology. (10th February 2022) - Scheibe, Franziska; Ostendorf, Lennard; Prüss, Harald; Radbruch, Helena; Aschman, Tom; Hoffmann, Sarah; Blau, Igor‐Wolfgang; Meisel, Christian; Alexander, Tobias; Meisel, Andreas
Abstract: Background and purpose: A fraction of patients with antibody‐mediated autoimmune diseases remain unresponsive to first‐/second‐line and sometimes even to escalation immunotherapies. Because these patients are still affected by poor outcome and increased mortality, we investigated the safety and efficacy of the plasma cell‐depleting anti‐CD38 antibody daratumumab in life‐threatening, antibody‐mediated autoimmune diseases. Methods: In this retrospective, single‐center case series, seven patients with autoantibody‐driven neurological autoimmune diseases (autoimmune encephalitis, n  = 5; neurofascin antibody‐associated chronic inflammatory demyelinating polyneuropathy associated with sporadic late onset nemaline myopathy, n  = 1; seronegative myasthenia gravis, n  = 1) unresponsive to a median of four (range = 4–9) immunotherapies were treated with four to 20 cycles of 16 mg/kg daratumumab. Results: Daratumumab allowed a substantial clinical improvement in all patients, as measured by modified Rankin Scale (mRS; before treatment: mRS =5, n  = 7; after treatment: median mRS =4, range = 0–5), Clinical Assessment Scale in Autoimmune Encephalitis (from median 21 to 3 points, n  = 5), Inflammatory Neuropathy Cause and Treatment disability score (from 7 to 0 points, n  = 1), and Quantitative Myasthenia Gravis score (from 16 to 8 points, n  = 1). Daratumumab induced a substantial reduction of disease‐specific autoreactive antibodies, total IgG (serum, 66%, n  = 7; cerebrospinal fluid, 58%, n  = 5), and vaccine‐induced titers for rubella (50%) and tetanus toxoid (74%). Treatment‐related toxicities Grade 3 or higher occurred in five patients, including one death. Conclusions: Our findings suggest that daratumumab provided a clinically relevant depletion of autoreactive long‐lived plasma cells, identifying plasma cell‐targeted therapies as promising escalation therapy for highly active, otherwise treatment‐refractory autoantibody‐mediated neurological diseases. Abstract : A fraction of patients with antibody‐mediated autoimmune diseases remain unresponsive to first‐/second‐line and sometimes even to escalation immunotherapies. Because these patients are still affected by poor outcome and increased mortality, we investigated the safety and efficacy of the plasma cell‐depleting anti‐CD38 antibody daratumumab in life‐threatening, antibody‐mediated autoimmune diseases.